Argon and helium plasma coagulation of porcine liver tissue. (October 2017) - Glowka, Tim R; Standop, Jens; Paschenda, Pascal; Czaplik, Michael; Kalff, Jörg C; Tolba, René H
Objective: Argon plasma coagulation (APC) and helium plasma coagulation (HPC) are electrosurgical techniques that provide noncontact monopolar electrothermal haemostasis. Although these techniques have been widely used clinically during the last three decades, their in vivo effects on liver tissue remain unclear. Methods: We investigated the effects of different power levels (10–100 W) of APC and HPC on liver coagulation in 11 Landrace pigs. Capillary blood flow and capillary blood flow velocity were recorded with a combined laser Doppler flowmeter and spectrophotometer. The temperature, clinical biochemical parameters, blood gas parameters, bile duct-sealing effect, and coagulation depth were measured. Results: APC and HPC significantly reduced the capillary blood flow and capillary blood flow velocity compared with baseline flow. No significant temperature change was measured on the liver surface immediately after coagulation. The clinical biochemical and blood gas parameters were not different before and after coagulation. The coagulation depth was positively correlated with the device power setting. Conclusions: These results prove that APC and HPC provide sufficient superficial haemostasis. No significant systemic effects occurred following coagulation. The depth of the coagulation effect can be controlled through selection of the output power level.